Cu/Ce0.6Mn0.3Fe0.1O2-δ membrane fuel electrode fabricated by infiltration method for solid oxide electrochemical cells. (1st May 2017) - Liu, Limin; Wang, Yong; Zhou, Xiaoliang; Yang, Yixuan; Ma, Chao; Li, Yuan; Wang, Chen; Zhao, Xiaohong; Li, Bin
Abstract: A cermet fuel electrode Cu/Ce0.6 Mn0.3 Fe0.1 O2-δ (Cu/CMF) is proposed for a reversible solid oxide electrochemical cell (SOC) with CO/CO2 as the shuttle. Cu is inert for the carbon deposition and CMF is electrochemically active for CO oxidation and CO2 reduction. The electrode polarization resistances in CO at 700, 750 and 800 °C are 0.328, 0.207 and 0.155 Ω cm 2, respectively, presenting high electrochemical activity towards CO oxidation. The maximal power densities can reach up to 303.3, 482.2 and 691.9 mW/cm 2 at 700, 750 and 800 °C, respectively. When the reversible SOCs are operated in solid oxide electrolysis cell mode, the polarization resistance of the electrolysis cell for pure CO2 reduction at 800 °C has the minimal value of 0.126 Ω cm 2 at 1.8 V. At 2.0 V, the current densities can reach up to 0.584 1.219 and 2.204 A/cm 2 at 700, 750 and 800 °C, respectively. The durability of the cell in CO for as long as 200 h indicates the electrode has remarkable stability. And the short-term stability characteristics for CO2 electrolysis at different voltages illustrate that the cell performs well below 2.0 V. The harsh reducing environment at 2.0 V may be detrimental to the Cu/CMF electrode.